RELATIONSHIP BETWEEN CHILD NUTRITION STATUS, FATHER'S LAST EDUCATION LEVEL ANDMOTHER'S LAST EDUCATION LEVEL WITH STUDENT LEARNING OUTCOMES SDN PLOSOREJO 1 PLOSOREJO VILLAGE RANDUBLATUNG BLORA REGENCY - Rani Kartikasari (Jurnal EduHealth, 2021)
The problems studied in this study are how respondents describe based on the nutritional status of the child, the last level of education of the father, the last level of education of the mother, and the student's learning outcomes, whether there is a relationship between the child's nutritional status, the father's last level of education, and the mother's last level of education with student learning outcomes. The purpose of this study was to find out the respondent's picture based on the child's nutritional status, the father's last level of education, the mother's last level of education, the mother's last level of education, the mother's final education level, the student's learning outcome, and the relationship between the child's nutritional status, the father's last level of education, and the mother's last level of education with the student's learning outcomes. This type of research is an analytic survey with a case control design. The population is all elementary school students in grades 4, 5 and 6 who are in Plosorejo I Elementary School, a total of 85 children. The sample was 62, consisting of 31 case groups and 31 control groups. Sampling technique with restrictions. The instruments used in this study are stepped on scales (seca), microtoise, class list books, student raport books. Bivariate analysis with Chi Square statistical test and to find out the magnitude of risk factors used Odds Ratio analysis. The results stated that the nutritional status (BB /TB) of students in grades 4, 5, and 6 of Plosorejo I elementary school was mostly normal, in the case group by 87.1% and the control group by 61.2%, the nutritional status (TB/U) was mostly normal, in the case group by 74.2% and the control group by 67.8%, the father's last education level was mostly elementary school, in the case group by 25.8% and the control group by 38.8%, and the last level of education of the mother partly also graduated from elementary school, in the case group by 35.4% and in the control group by 42%. From the results of statistical tests showed that there was a significant relationship between nutritional status (BB/TB) and learning outcomes (p value=0.040 and OR=4,623), there was no significant association between nutritional status (TB/U) and student learning outcomes (p value=0.780 and OR=1,369), no relationship of father's last education level with student learning outcomes (p value=0.786 and OR=0.744), and there was no significant association between the mother's last level of education and the student's learning outcomes (p value=0.057 and OR=0.291). The conclusion that can be taken is that there is a significant relationship between nutritional status (BB / TB) with learning outcomes, no significant association between nutritional status (TB / U) with student learning outcomes, no relationship of paternal education level with student learning outcomes, and no significant relationship between maternal education level and student learning outcomes.